AKTIVITAS BEBERAPA SENYAWA TURUNAN BENZOPIRAN (CHROMONES) DAN BENZOFURANON (COUMARANONES) TERHADAP Steinernema feltiae (The Activities of Benzopyran (Chromones) and Benzofuranones (Coumaranones) Derivatives against Steinernema feltiae) - Khairan Khairan; Muhammad Bahi; Claus Jacob; Rinaldi Idroes (Jurnal Kedokteran Hewan, 2016)
This study was purposed to inquire the activities of benzopyran (chromones) and benzofuranones (coumaranones) derivatives against Steinernema feltiae (S. feltiae). The toxicity assay against S. feltiae showed that benzopyran derivatives 2, 3, 4, 6, and 9 have the highest activity on S. feltiae with viabilities percentage of 50%. The compound 9 demostrated the highest activity with LD 50 and LD values, 7.2 and 52.2 μM, respectively. The activities of compound 7 and 10 showed the lowest toxicity. Interestingly, the activity of benzofuranone derivatives showed significant activities against S. feltiae. Compare to benzopyran derivatives, the benzofuranone derivatives has the highest toxicity, in particular compound 13 with LD 5.45 μM. The nematicidal assay showed that benzofuranones (coumaranones) derivatives revealed higher activities than benzopyran (chromones) derivatives.Key words: chromones, benzopyran, coumaranones, benzofuranone, and Steinernema feltiae